Quantitative easing and the price-liquidity trade-off - Marien Ferdinandusse; Maximilian Freier; Annukka Ristiniemi (Sveriges Riksbank, 2017)
We present a search theoretic model of over-the-counter debt with quantitative easing (QE). The impact of central bank asset purchases on yields depend on market tightness, which is determined by shares of preferred habitat investors. The model predicts that the impact of government bond purchases is higher in countries with a higher share of preferred habitat investors. Furthermore, there is a trade-off with liquidity, which is not present in other models of QE. We present a new index for the share of preferred habitat investors holding government bonds in Eurozone countries, based on the ECB's securities and holdings statistics, which we use to match the impact of QE on the observed yield changes in data and to test our model.
Keywords: E52; E58; G12; 330; Quantitative easing; liquidity; search and matching